Numbering action vertices in workflow graphs - Mann, Zoltán Ádám (Zielona Góra: Uniwersytet Zielonogórski)
Workflow graphs, consisting of actions, events, and logical switches, are used to model business processes. In order to easily identify the actions within a workflow graph, it is useful to number them in such a way that the numbering reflects the structure of the workflow. However, available tools offer only rudimental numbering schemes. In the paper, a set of natural requirements is defined that a logical numbering should fulfill. It is investigated under what conditions there is an appropriate numbering at all, when it is uniquely defined by the set of requirements, and when it can be computed efficiently.
Keywords: workflow graph; flowchart; event-driven process chain; numbering; depth-first search